Catatonia as a Result of a Traumatic Brain Injury - Jessica Berthelot; Jacob Cambre; Madeline Erwin; Jennifer Phan (Case Reports in Psychiatry)
Catatonia is a neuropsychiatric syndrome typically marked by disturbances in motor activity, speech, and behavior. It has historically been associated with psychiatric illness, but acute medical illness, neurocognitive disorders, and neurodevelopmental disorders can cause catatonia as well. Catatonia is likely underrecognized and underdiagnosed in the general medical hospital, despite high risks of morbidity and mortality and the availability of rapidly effective treatment. Here, we present a case of catatonia secondary to traumatic brain injury that responded to lorazepam after a delayed diagnosis. A young male patient who was incarcerated and assaulted was sent to the emergency department multiple times for unresponsive and unpredictable behavior, including not agreeing to be released home. After being admitted with the diagnosis of postconcussive syndrome, he was ultimately diagnosed with catatonia, and intravenous lorazepam resulted in a return to his baseline mental status. We discuss factors that led to the delay in diagnosis, including lack of training in recognition of catatonia, suspicion of feigned symptoms for secondary gain, and the implication of stigma in an African American young male arrested for a drug-related crime.